Business Performance Model of Butcher Shop Entrepreneur in Thailand - Chancharoen, Pattarapong; Pranee, Supattra; Pungnirund, Bundit (The Journal of Development Administration Research, 2024)
This research aimed to study 1) the levels of entrepreneurial orientation, total quality management, innovation, dynamic capability, competitive advantage, and business performance, 2) Influence of entrepreneurial orientation, total quality management, innovation, dynamic capability, and competitive advantage towards business performance, and 3) business performance of the butcher shop entrepreneur model development. This research employed mixed-method techniques and quantitative method; the sample group of this research was 420 entrepreneurs using a proportional stratified random sampling by each region. Data collection referred to a questionnaire and analyzed data by mean, standard deviation and structural equational modeling analysis. In addition, this qualitative research used focus group discussion. Including executives or managers of stores selling meat products with working experience of 5 years or more, and executives of related government agencies, totaling 15 people, in-depth analysis was conducted using content analysis. The research found that 1) levels of entrepreneurial orientation, total quality management, innovation, dynamic capability, competitive advantage, and business performance were the highest. 2) total quality management, innovation, and competitive advantage significantly influenced the business performance with a significance level of.05, and 3) business performance of the butcher shop entrepreneur in Thailand model developed by the researcher was namely TIC ED Model (T = Total quality management, I = Innovation, C = Competitive advantage, E = Entrepreneurial orientation D = dynamic capability)